Merit system in promotion of primary high leadership positions in Majene regency - Muhammad salim Alimuddin; Sangkala Sangkala; Badu Ahmad (Institute of Computer Science (IOCS), 2024)
The aim of this research is to find out the promotion mechanism for Pratama high leadership positions, whether a merit system has been implemented or not. The mechanism for promoting Primary high leadership positions in the Majene Regency regional government illustrates the principle of a merit system. At each level, promotions are held to become pratama high leaders due to vacancies in positions caused by the retirement of officials, transfers of officials and deaths of officials filling the positions. The principle of openness to all can be seen in information about job vacancies via social media, electronic media and print media covering the West Sulawesi region, but on the contrary, the principle of the best candidate in making the regent's decision as a regent candidate. The Civil Service Development Officer (PPK) has not presented a merit system because when announcing the list of names of the top three participants from the final selection results, the selection committee did not transparently announce the participants' scores, but only announced the names of the participants based on the alphabetical order of the first letter of the participants and at the stage of determining the selected participants. , the Personnel Development Officer (PPK) is given authority or prerogative. appoint 1 (one) person from the 3 (three) names proposed by the selection committee. This is what participants complained about because the action seemed less objective and transparent. This research uses qualitative methods with interview techniques, where the committee and participants are informants